The Increase in VO2 Max and Passing Using Exercise Small-Sided Game 3 vs 3 and 6 vs 6 On Football Players - Maujud, Muhammad Fajri; Afandi, Zainal; Pratama, Budiman Agung (UNIVERSITAS NEGERI MAKASSAR, 2021)
The purpose of this study was to determine the increase in vo2max and passing skills using small-sided games 3 vs 3 and 6 vs 6 exercises in soccer players. This study uses a quantitative approach, the type of research is experimental research, the sample used is 51 football players in Trenggalek under-14 who were selected randomly, this research was carried out in Trenggalek district, namely the Siwalan field, Sumbergedong field, and Sumberagung field, the instrument in the study This study uses a multistage fitness test and a passing test in football, data analysis uses the Manova test. The results showed that there was a difference between the small-sided games 3 vs 3 exercise group and the 6 vs 6 small-sided games group to increase vo2max with a sig value. 0.031 < 0.05, and there is a difference between the small-sided games 3 vs 3 practice group and the 6 vs 6 small-sided games group to improve passing with a sig value of 0.027 < 0.05. It can be concluded that overall small-side game exercises 3 vs 3 and 6 vs 6 can increase vo2max and passing for football players.